A test on methods for Mc estimation and spatial-temporal distribution of b-value in the eastern Tibetan Plateau - Gong, Weicheng; Chen, Huayuan; Gao, Yajing; Li, Qing; Sun, Yunqiang (Frontiers in Earth Science, 2024)
Seismic b-value is one of the most important parameters for seismological research and seismic hazards assessment, while the accuracy of the b-value largely depended on the completeness of seismic catalog. This article compares eight methods for estimating the minimum magnitude of completeness (Mc). The results indicate that the modified maximum curvature method (MMAXC), exhibits greater stability and accuracy, closely approximating the standard Mc obtained from the synthetic seismic catalogs. We then calculate the b-value using the instrumental seismic catalog from 2000-2023 in the eastern Tibetan Plateau. The results indicate that the five major earthquakes occur in regions with lower b-value. In addition, the temporal evolution of b-value before and after major earthquakes exhibits a common trend of decreasing before earthquakes, and increasing after earthquakes, which may reflect the stress accumulation and release during earthquakes. Combining the results of maximum shear strain rate and b-value, we identify five regions characterized by low b-value and high shear strain rate, indicating a higher potential seismic hazard in the future.